Estratégia emergente na lógica da multidão: uma abordagem a partir de iniciativas da multidão, do comum e da Teoria Ator-Rede. - Luz, Lucas Henrique da (Universidade do Vale do Rio dos Sinos, 2016)
Changes in the society and the organizational environment have given rise to different forms of thinking strategy over time. In this sense, the present dissertation seeks to analyze how the context of interaction, connectivity and cooperation favors or not the adoption of an emerging strategy in the logic of the crowd, with methodological contributions by the Actor-Network Theory (ANT). For this, we have conducted a qualitative research with an exploratory approach to analyzing two cases: Espaço Comum Luiz Estrela (ECLE) and Movimiento 15 de Mayo (15M), which act in environments marked by such characteristics. We conclude that the strategizing of the cases studied assumes a logic of crowd for being emerging and self-organized, a result of interactions between the human and non-human practitioners (singularities), legitimizing themselves in the form of a spiral and having governance as openness. It is a strategizing marked by the use of information and communication technologies and by a more direct participation, where interactions and agencies occur through the differences and the commons under a perspective of the uno through the multiple – agencies and interactions in the logic of the crowd. They are characteristics that do not constitute a model, but a logic of strategizing and take up different shapes in the cases studied. We also come to the conclusion that the methodological inspirations by the ANT, such as looking reality in a non-essentialistic way in a performative logic, valuing differences and considering the agency of human and non-human actors, are appropriate for the study of this strategy logic. Furthermore, we affirm that the present dissertation contributes to advancing theoretically in the forms of thinking the agencies, the relationships between micro-actions and micro-contexts, as well as to the understanding of the mystery, experimentation and differences as a strategic power. It also advances by building a strategy in the logic of the crowd suitable for complex contexts, typical of the current moment, and suggesting methodological inspirations for its apprehension and analysis. Finally, this study allows the organizations studied a better comprehension of their strategic practices and their power.
Keywords: Estratégia emergente; Estratégia como prática; Multidão; Comum; Teoria ator-rede; Emerging strategy; Strategy as practice; Crowd; Commons; Actor-network theory; ACCNPQ::Ciências Sociais Aplicadas::Administração